Recellularization of decellularized adipose tissue-derived stem cells : role of the cell-secreted extracellular matrix in cellular differentiation - Guneta, Vipra (2020)
Adipose-derived stem cells (ASCs) are found in a location within the adipose tissue known as the stem cell niche. The ASCs in the niche are maintained in the quiescent state, and upon exposure to various microenvironmental triggers are prompted to undergo proliferation or differentiation. These microenvironmental triggers also modulate the extracellular matrix (ECM), which interacts with the cells through the cytoskeleton and induces downstream events inside the cells that bring about a change in cell behaviour. In response to these changes, the cells remodel the ECM, which will differ according to the type of tissue being formed by the cells. As the ECM itself plays an important role in the regulation of cellular differentiation, this study aims to explore the role of the cell-secreted ECM at various stages of differentiation of stem cells in triggering the differentiation of ASCs. To this end, the ASCs cultured in proliferation, osteogenic and adipogenic media were decellularized and the secreted ECM was characterized. Overall, it was found that osteo-differentiated ASCs produced higher amounts of collagen and glycosaminoglycans (GAG) compared to the undifferentiated and adipo-differentiated ASCs. The two types of differentiated ECMs were subsequently shown to trigger initial but not terminal differentiation of ASCs into osteo- and adipo-lineages respectively, as indicated by the upregulation of lineage specific markers. In addition, integrin subunits alpha (α) 6 and integrin beta (β) 1 were found to be produced by ASCs cultured on cell-secreted ECM-coated substrates, suggesting that the integrins α6 and β1 play an instrumental role in cell–ECM interactions. Taken together, this study demonstrates the importance of the ECM in cellular fate decisions and how ECM-coated substrates can potentially be used for various tissue engineering applications.